Atomic force microscope observation of athletes’ hemoglobin imaging - Zhang, Guojun; Luo, Weidong; Hajee, Shereen Ismail; Gong, HanCheng (Cellular and Molecular Biology, 2020)
Hemoglobin (Hb) is a protein and its functional form has a tetrameric structure. This structure is the result of a combination of four sub-units called globin and indicates the dynamic interaction between them. Each subunit has a ring-shaped organic molecule called a heme that contains an iron atom; Heme is a group that mediates the reversible binding of oxygen by hemoglobin. This research was performed to observe the image of Hb by an atomic force microscope (AFM) and measure the physical function of athletes. For this purpose, based on the principle of AFM imaging, the hemoglobin crosslinking method was used to measure the morphology and size of cross-linked Hb, glutaraldehyde and Hb diameter were detected to prepare cross-linked Hb samples with different molar ratio, the activity of peroxidase was detected by Trinder reaction. The AFM was used to detect the influence of physiological environment changes such as pH, temperature, oxygen partial pressure and osmotic pressure on the absorption spectrum of Hb imaging. Results showed that the size of the uncrosslinked Hb was 6.64 nm. With the increase of the molar ratio of glutaraldehyde to Hb, the number of Hb molecules involved in the crosslinking increased, and the molecular size increased. During the crosslinking process, the aggregation of the cross-linked molecules would make the particle size of some Hb molecules reach 80-100 nm. The peak height, peak position and peak shape of the characteristic absorption peaks of pH to hemoglobin at 550 and 589 nm occurred. When the temperature changes continuously in the range of 30-55â„ƒ, the peak height of Hb absorption spectrum of normal red blood cells at 550 nm and 589 nm decreases gradually with the increase of temperature, and the peak shape at 610 nm changes obviously at 42â„ƒ, which indicates that the molecular structure of Hb changes; the absorption spectrum curve of deoxygenation disappears at 500 nm, the oxygen-binding capacity of Hb is very low, and the oxygen affinity and oxygenated hemoglobin are low (The concentration of HbO2) decreased, the osmotic pressure increased, the RBC dehydrated, the volume decreased, and the concentration of Hb increased. Conclusion: It is more accurate and comprehensive to use AFM to observe athletes’ hemoglobin.